2017
DOI: 10.2166/wst.2017.248
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal tolerance and removal potential in mixed-species biofilm

Abstract: The aim of the study was to examine heavy metal tolerance (Cd, Zn, Ni and Cu) of single- and mixed-species biofilms (Rhodotorula mucilaginosa and Escherichia coli) and to determine metal removal efficiency (Cd, Zn, Ni, Cu, Pb and Hg). Metal tolerance was quantified by crystal violet assay and results were confirmed by fluorescence microscopy. Metal removal efficiency was determined by batch biosorption assay. The tolerance of the mixed-species biofilm was higher than the single-species biofilms. Single- and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In our previous investigations, we concluded that R. mucilaginosa biofilm was few times more tolerant and had a higher potential for removing Hg 2+ , Cu 2+ and Pb 2+ ions than planktonic cells (GRUJIĆ et al 2017a). Furthermore, the R. mucilaginosa/Escherichia coli mixed biofilm was more efficient in removing heavy metals than their mono-species biofilms (BUZEJIĆ et al, 2016, GRUJIĆ et al, 2017b. These findings led to the further development of studies on the Cd 2+ , Zn 2+ and Ni 2+ ion tolerance and removal efficiency of planktonic cells and biofilm of R. mucilaginosa and Saccharomyces boulardii, including comparative analysis with the previously obtained results.…”
Section: Introductionmentioning
confidence: 62%
“…In our previous investigations, we concluded that R. mucilaginosa biofilm was few times more tolerant and had a higher potential for removing Hg 2+ , Cu 2+ and Pb 2+ ions than planktonic cells (GRUJIĆ et al 2017a). Furthermore, the R. mucilaginosa/Escherichia coli mixed biofilm was more efficient in removing heavy metals than their mono-species biofilms (BUZEJIĆ et al, 2016, GRUJIĆ et al, 2017b. These findings led to the further development of studies on the Cd 2+ , Zn 2+ and Ni 2+ ion tolerance and removal efficiency of planktonic cells and biofilm of R. mucilaginosa and Saccharomyces boulardii, including comparative analysis with the previously obtained results.…”
Section: Introductionmentioning
confidence: 62%
“… Golby et al (2014) found that Rhodococcus erythropolis isolated from the community was less tolerant in the presence of metals compared to mixed biofilm, so it was unable to perform biomineralization of metals. By comparing the individual and mixed biofilms of Rhodotorula mucilaginosa and Escherichia coli, Grujić et al (2017b) found a higher resistance of mixed biofilms to the presence of HMs. Scientists confirmed that different regulatory processes (biochemical and genetic) take place within the biofilm that allow microorganisms to develop a better mechanism of tolerance and improve their resistance in the presence of HMs ( Harrison et al, 2007 ).…”
Section: Discussionmentioning
confidence: 96%
“…The direct colony approach was used to create a microorganism suspension. The turbidity of the suspension was adjusted using a densitometer (DEN-1, Biosan, Latvia), McFarland 1.0, to equate to 10 8 CFU/ml for bacteria and 10 6 CFU/ml for yeasts ( Grujić et al, 2017b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotrophic bacteria such as P. aeruginosa [ 74 ] and Klebsiella pneumoniae [ 75 ] show significantly increased resilience to many antibiotics in intact biofilms compared to planktonic cultures. Although the non-infectious cyanobacteria are less likely to encounter antibiotic treatment, the same principle of EPS shielding cells from harmful extraneous effects has been extended to salt and metal ion toxicity [ 76 , 77 , 78 ], phage infection [ 79 ], and predation by some (though not all) grazers [ 80 ]. Work on the Pseudomonas genus has shown that functional, retractile T4P are also required for infection by a number of bacteriophages [ 81 , 82 , 83 ].…”
Section: Many Species Of Cyanobacteria Form Large-scale Multicellumentioning
confidence: 99%